Microbial Community Interactions Are Sensitive to Small Changes in Temperature - Burman, Emil; Bengtsson-Palme, Johan (Frontiers in Microbiology, 2021)
Microbial communities are essential for human and environmental health, often forming complex interaction networks responsible for driving ecosystem processes affecting their local environment and their hosts. Disturbances of communities can lead to loss of interactions and thereby important ecosystem functionality. The research on what drives interactions in microbial communities is still in its infancy and much information has been gained from the study of model communities. However, these model microbial communities are often cultured under controlled conditions and it is not well known how fluctuations abiotic factors such as temperature affect their interaction networks. In this work, we have studied the effect of temperature on interactions between the members of the model community THOR, which is formed by three bacterial species: Pseudomonas koreensis Flavobacterium johnsoniae and Bacillus cereus. Our results show that those interactions are highly dependent on incubation temperature, with an optimal temperature for maximum community interaction at 18ºC. We also found that THOR biofilms had remarkably different abundances of its members when grown at 11, 18 and 25°C. The results suggest that community interactions are highly sensitive to changes in temperature, and that this sensitivity is largely related to different growth rates of the individual members at different temperatures. Our findings likely extend to other microbial communities and environmental parameters. Thus, temperatures could affect community stability and may affect diverse processes including soil productivity, bioprocessing and disease suppression. Moreover, to establish reproducibility between laboratories working with microbial model communities, it is crucial to ensure experimental stability, including carefully managed temperature conditions.